Impact of Artificial Intelligence Development on Taiwan’s Legal System and Legislation in the Post-Pandemic Era - Chang, Li-Ching (International Journal of Membrane Science and Technology, 2024)
In the post-pandemic era, AI development has entered a new phase, driven by the emergence of generative AI and the increasing prevalence of information and communication technologies represented by 5G. In the dawn of the AI age, significant shifts are underway, heralding a new era of transformation. This article explores the impact of AI advancement on Taiwan’s legal framework during this era. It delves into both historical developments and prospective transformations and begins with a retrospective analysis of Taiwan’s AI-related legislation before the post-pandemic era. Subsequently, it focuses on a critical aspect of Taiwan’s AI legal framework during this era, including two pivotal documents in Taiwan: the "AI Basic Act" and the " Reference Guidelines for the Use of Generative AI in the Executive Yuan and its Subordinate Agencies and Affiliated Institutions”. Both have recently garnered widespread attention, marking a crucial step towards navigating the evolving landscape of artificial intelligence. Finally, this article offers insights into the prospective evolution of Taiwan’s legal landscape pertaining to AI. The formulation of the "AI Basic Act" is pivotal in setting fundamental norms for AI development in Taiwan. This draft is significant with its 24 articles aimed at fostering a trustworthy environment and promoting diverse AI utilization. It ensures that Taiwan’s high-tech advancements align with global standards. On the other side, the “Reference Guidelines for the Use of Generative AI” are designed to regulate the administrative agencies in response to the widespread application of generative AI. Furthermore, since 2023, the Personal Data Protection Act and Criminal Code, among others, have all been amended to include provisions related to AI technology, reflecting the apparent impact of AI on the legal system. Given the novelty of AI in society, prioritizing the creation of a basic act is crucial. Such legislation defines AI in Taiwan, establishes ethical principles, outline development directions, and provides fundamental norms. It will serve as a cornerstone for shaping and revising other policies and laws to navigate the evolving landscape of AI.